Terraforming: Ecopolitical Transformations and Environmentalism in Science Fiction - Pak, Chris (Liverpool University Press, 2016)
Terraforming is the process of making other worlds habitable for human life. Its counterpart on Earth - geoengineering - is receiving serious consideration as a way to address climate change. Contemporary environmental awareness and our understanding of climate change is influenced by science fiction, and terraforming in particular has offered scientists, philosophers, and others a motif for thinking in complex ways about our impact on planetary environments. This book asks how science fiction has imagined how we shape both our world and other planets and how stories of terraforming reflect on science, society and environmentalism.